Extreme miniaturization of a new amniote vertebrate and insights into the evolution of genital size in chameleons - Frank Glaw (Nature Portfolio, 2021)
Abstract Evolutionary reduction of adult body size (miniaturization) has profound consequences for organismal biology and is an important subject of evolutionary research. Based on two individuals we describe a new, extremely miniaturized chameleon, which may be the world’s smallest reptile species. The male holotype of Brookesia nana sp. nov. has a snout–vent length of 13.5 mm (total length 21.6 mm) and has large, apparently fully developed hemipenes, making it apparently the smallest mature male amniote ever recorded. The female paratype measures 19.2 mm snout–vent length (total length 28.9 mm) and a micro-CT scan revealed developing eggs in the body cavity, likewise indicating sexual maturity. The new chameleon is only known from a degraded montane rainforest in northern Madagascar and might be threatened by extinction. Molecular phylogenetic analyses place it as sister to B. karchei, the largest species in the clade of miniaturized Brookesia species, for which we resurrect Evoluticauda Angel, 1942 as subgenus name. The genetic divergence of B. nana sp. nov. is rather strong (9.9‒14.9% to all other Evoluticauda species in the 16S rRNA gene). A comparative study of genital length in Malagasy chameleons revealed a tendency for the smallest chameleons to have the relatively largest hemipenes, which might be a consequence of a reversed sexual size dimorphism with males substantially smaller than females in the smallest species. The miniaturized males may need larger hemipenes to enable a better mechanical fit with female genitals during copulation. Comprehensive studies of female genitalia are needed to test this hypothesis and to better understand the evolution of genitalia in reptiles.